Actividad de beta-galactosidasa como marcador de senescencia en cultivos primarios del epitelio de la superficie ovárica (2010)
beta-galaetosidase activity reflects the rate of cellular aging in vitro. Such activity was quantified at pH 6 in ovarian epithelial cells from 28 donors without a history of cancer, by the chemoluminiscent method. The cells were serially cultured until they achieved the state of permanent growth arrest. During the exponential growth phase, all cultures showed a similar pattern of growth and low beta-galitetosidase activity. However, both in the onset of decrease replicative activity, as well as in the onset of the stationary phase, there was a significant rise in the enzyme activity. Our results showed that P-galactosidase activity can be considered as a replicative senescence marker of the ovarian surface epithelium at pH 6.